2016
DOI: 10.1016/j.smrv.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the mean: A systematic review on the correlates of daily intraindividual variability of sleep/wake patterns

Abstract: Features of an individual's sleep/wake patterns across multiple days are governed by two dimensions, the mean and the intraindividual variability (IIV). The existing literature focuses on the means, while the nature and correlates of sleep/wake IIV are not well understood. A systematic search of records in five major databases from inception to November 2014 identified 53 peer-reviewed empirical publications that examined correlates of sleep/wake IIV in adults. Overall, this literature appeared unsystematic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
296
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(314 citation statements)
references
References 77 publications
15
296
2
1
Order By: Relevance
“…This within-person approach is motivated by calls to increase our understanding of the dynamics involved in substance abuse recovery (McKay et al, 2006; Shiffman, 2009), at the micro, daily level (Zheng et al, 2015). The need for this approach is further underscored by findings of day-to-day variability in the constructs of craving, affect, and sleep (Bei et al, in press; Cleveland & Harris, 2010; Peacock et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This within-person approach is motivated by calls to increase our understanding of the dynamics involved in substance abuse recovery (McKay et al, 2006; Shiffman, 2009), at the micro, daily level (Zheng et al, 2015). The need for this approach is further underscored by findings of day-to-day variability in the constructs of craving, affect, and sleep (Bei et al, in press; Cleveland & Harris, 2010; Peacock et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies utilizing experimental and naturalistic designs have demonstrated associations between sleep duration and various components of the cortisol diurnal rhythm including the cortisol awakening response (CAR; e.g., Kumari et al, 2009; Vargas and Lopez-Duran, 2014) and the linear decline across the waking day (e.g., Zeiders et al, 2011; Kumari et al, 2009; Castro-Diehl et al, 2015), yet other studies have identified no associations between sleep duration and diurnal cortisol (e.g., Pruessner et al, 1997; Federenko et al, 2004). Although prior empirical studies have primarily focused on sleep duration, recent calls in the literature have recognized the need to examine other facets of sleep (Dijk, 2012; Bei et al, 2016), including sleep quality and day-to-day fluctuations in sleep patterns (i.e., sleep variability). However, few studies have explicitly examined associations between sleep quality and variability and the diurnal patterns of cortisol.…”
Section: Introductionmentioning
confidence: 99%
“…We selected a simple model for illustrative purposes, but more sophisticated models can include covariates (e.g., age, partner status, BMI) to examine the impact of these variables on the mean and IIV of sleep efficiency or other sleep parameters. Such analyses can be used to test specific hypotheses and develop a theoretical framework for the antecedents and consequences of IIV, as recommended by Bei et al 3 Furthermore, the model could be used to explore different trajectories of change in IIV over time by treating time as a polynomial factor rather than a linear factor. This could yield important patterns regarding the patient's sleep experience during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these analyses frequently did not control for the mean values when examining IIV. 3 Therefore, the authors recommended a two-dimensional approach when analyzing longitudinal sleep data that includes the mean as one dimension and the IIV as a second dimension. 3 Recently, a novel statistical technique called the locationscale mixed model has emerged which appears particularly well-suited for examining the mean and IIV as different dimensions of the sleep experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation